Spatial-based scenario analysis for the smart energy transition - (:unkn) unknown (AESOP, 2019)
Scenario analysis is a particularly interesting tool for the smart energy transition of cities and regions. It allows understanding the possible futures of an energy system with and without the implementation of strategic actions and under different conditions. The presented study deals with the development of alternative scenarios for the energy system of Valle d’Aosta region (Italy) and is aimed at suggesting sustainable pathways for its energy transition. In particular, the strategic actions want to foster the exploitation of Shallow Geothermal Energy (SGE), a renewable source still not exploited adequately in spite of its great potential to increase the energy efficiency in buildings. Two driving forces establish the base for the scenario development. T hey a re: 1 ) u sing S GE f or supplying the space heating demand of residential buildings, replacing some fossil fuels; 2) refurbishing part of the residential building stock for decreasing its thermal demand. Different combinations of these two drivers shape the developed scenarios, which are then analysed through some indicators. All the data processing is done following a spatially explicit approach. This GIS-based scenario analysis can support the decision-makers during the planning process allowing them to analyse from various viewpoints the alternative scenarios and to prioritise the different energy measures.
Planning for Transition – book of proceedings 31; 2
Keywords: energy transition; scenario analysis; GIS-based approach